Assessing Tax Auditors’ Understanding of Reinvestment Allowance in Malaysia - Ibrahim, Idawati; Saad, Mohd Shukri; Abdul Aziz, Saliza (2024)
Tax auditing is one of the main activities in promoting tax compliance. Therefore, ensuring the highest standards of tax knowledge among tax auditors on issues such as reinvestment allowance (RA) incentive is crucial in achieving highest audit quality. Differing interpretations of the act by the tax auditors may lead to inconsistency in tax audit judgement. In relation to this issue, this study is conducted to investigate the level of understanding on RA among tax auditors in the Inland Revenue Board of Malaysia (IRBM). A qualitative method is utilised to achieve the study objective by conducting interviews with 20 tax auditors through an online platform. Through a thematic analysis, this research reveals various points of view, explaining the level of understanding on RA among the IRBM tax auditors. Findings show a variable level of understanding of RA among officers, with a notable disparity between those with years of experience in taxation and newer officers. The study concludes that while there is foundational awareness of RA among tax auditors in the IRBM, there is a need for enhanced and ongoing education to ensure comprehensive understanding and effective implementation of RA policies